Bayesian Comparison of Bivariate Copula-GARCH and MGARCH Models - Mokrzycka, Justyna (Central European Journal of Economic Modelling and Econometrics, 2019)
The aim of the study is to formally compare the explanatory power of CopulaGARCH and MGARCH models. The models are estimated for logarithmic daily rates of return of two exchange rates: EUR/PLN, USD/PLN and stock market indices: SP500, BUX. The analysis is performed within the Bayesian framework. The posterior model probabilities point to AR(1)-tSBEKK(1,1) for the exchange rates and VAR(1)-tCopula-GARCH(1,1) for the stock market indices, as the superior specifications. If the marginal sampling distributions are different in terms of tail thickness, the Copula-GARCH models have higher explanatory power than the MGARCH models.